Early literacy experiences constrain L1 and L2 reading procedures - Bhide, Adeetee (Frontiers in Psychology, 2015)
Computational models of reading posit that there are two pathways to word recognition, using sublexical phonology or morphological/orthographic information. They further theorize that everyone uses both pathways to some extent, but the division of labor between the pathways can vary. This review argues that the first language one was taught to read, and the instructional method by which one was taught, can have profound and long-lasting effects on how one reads, not only in one’s first language, but also in one’s second language. Readers who first learn a transparent orthography rely more heavily on the sublexical phonology pathway, and this seems relatively impervious to instruction. Readers who first learn a more opaque orthography rely more on morphological/orthographic information, but the degree to which they do so can be modulated by instructional method. Finally, readers who first learned to read a highly opaque morphosyllabic orthography use less sublexical phonology while reading in their second language than do other second language learners and this effect may be heightened if they were not also exposed to an orthography that codes for phonological units during early literacy acquisition. These effects of early literacy experiences on reading procedure are persistent despite increases in reading ability.